Adubação nitrogenada e aplicação de herbicidas como reguladores de crescimento em grama esmeralda - Dinalli, Raíssa Pereira [UNESP] (2014)
Nitrogen (N) is essential to nutrition and maintenance intense green color of turfgrasses. However, increases the growth of shoots and, consequently, the frequency of cuts, the main factor in the cost of turfgrasses maintenance. In this context, this study aimed to evaluate the nitrogen fertilization and the potential use of herbicides as growth regulators on zoysiagrass (Zoysia japonica Steud.) on an Ultisol, to maintain the turfgrass with good visual quality and nutrition as well as reduce foliar growth. The research was conducted at the Experimental Station of UNESP, Ilha Solteira/SP from June 2012 to December 2013. It was used a randomized block design with 20 treatments arranged in a factorial scheme 5 x 4 with four replications, being four herbicides: glyphosate, imazaquin, imazethapyr and metsulfuron-methyl (applied at the rate of respectively, 200, 420, 80 and 140 g ha-1 active ingredient (a. i.)) besides a control and four N rates, using urea as a source: 0, 5, 10 and 20 g m- 2 split in five times during the year. The turfgrass was irrigated by sprinkler. Were evaluated: the chemical characteristics of the soil, length and dry matter of leaves, leaf area, ICF index (leaf chlorophyll), the digital image analysis, the percentage of phytotoxicity of the shoot, the concentration and accumulation of macro and micronutrients by the leaves of turfgrass. Nitrogen rates of 10 to 20 g m-2 provided intense green color and sufficient nutrients content to maintain zoysiagrass. The herbicides metsulfuron-methyl and glyphosate stand out in control of the leaf length, the second did not sacrifice esthetic quality of the turfgrass, standing out as herbicide that can be used as a growth regulator of zoysiagrass at the rate of 200 g ha-1 of a. i